Tolerance and M2 (alternative) macrophage polarization are related processes orchestrated by p50 nuclear factor kappaB - Porta, Chiara; Rimoldi, Monica; Raes, Geert; Brys, Lea; Ghezzi, Pietro; Di Liberto, Diana; Dieli, Francesco; Ghisletti, Serena; Natoli, Gioacchino; De Baetselier, Patrick; Mantovani, Alberto; Sica, Antonio (Proceedings of the National Academy of Sciences - PNAS, 2009)
Cells of the monocyte-macrophage lineage play a central role in the orchestration and resolution of inflammation. Plasticity is a hallmark of mononuclear phagocytes, and in response to environmental signals these cells undergo different forms of polarized activation, the extremes of which are called classic or M1 and alternative or M2. NF-kappaB is a key regulator of inflammation and resolution, and its activation is subject to multiple levels of regulation, including inhibitory, which finely tune macrophage functions. Here we identify the p50 subunit of NF-kappaB as a key regulator of M2-driven inflammatory reactions in vitro and in vivo. p50 NF-kappaB inhibits NF-kappaB-driven, M1-polarizing, IFN-beta production. Accordingly, p50-deficient mice show exacerbated M1-driven inflammation and defective capacity to mount allergy and helminth-driven M2-polarized inflammatory reactions. Thus, NF-kappaB p50 is a key component in the orchestration of M2-driven inflammatory reactions.